2001
DOI: 10.1080/00036840010015066
|View full text |Cite
|
Sign up to set email alerts
|

Export–led growth and structural change: evidence from Malaysia

Abstract: Many studies have tried to establish the causal link between export expansion and economic growth. This contribution is to recognize that structural changes will change the sources of growth and this will affect the export-growth relationship. A country case study approach is used focusing on Malaysia, a country with one of the world's highest sustained growth rates and a long history of commodity trade. We use VAR analysis of Malaysian quarterly trade and GDP growth from 1965 to 1996. Trade data are disaggreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 26 publications
6
31
0
3
Order By: Relevance
“…As a summary, based on the findings of the short run causality test, we concluded that the hypothesis of export-led growth is still valid in the Malaysian economy as there appeared to be a positive relationship and short run causality running from the exports to growth. This study is consistent with the previous studies done by Shah and Yusoff (1990), Ghatak and Price (1997), Khalafalla and Webb (2001), and Choong et. al.…”
Section: Malaysiasupporting
confidence: 83%
See 1 more Smart Citation
“…As a summary, based on the findings of the short run causality test, we concluded that the hypothesis of export-led growth is still valid in the Malaysian economy as there appeared to be a positive relationship and short run causality running from the exports to growth. This study is consistent with the previous studies done by Shah and Yusoff (1990), Ghatak and Price (1997), Khalafalla and Webb (2001), and Choong et. al.…”
Section: Malaysiasupporting
confidence: 83%
“…This result is contradicted with the study done by Rahman and Mustafa (1997) that stated Indonesia experienced unidirectional causality from growth to exports both in short run and long run. In Malaysia, Khalafalla and Webb (2001) examine the relationships between exports and economic growth in Malaysia using quaterly data from first quater of 1965 until fourth quater of 1996. By using cointegration and Granger causality test, they found that ELGH was valid for both full sample and import substitution period.…”
Section: Empirical Studies Reviewmentioning
confidence: 99%
“…The export-led growth hypothesis was confirmed only in Malaysia. Khalafalla and Webb (2001) confirmed the export-led growth hypothesis in Malaysia for the period 1965-1980 while the growth-led exports hypothesis holds for the period [1981][1982][1983][1984][1985][1986][1987][1988][1989][1990][1991][1992][1993][1994][1995][1996]. In the case of India, Chandra (2002) found bidirectional causal relationship between export growth and GDP growth only in short run, while Chandra (2003) found bidirectional causal relationship between the two variables in the long run.…”
Section: Introductionmentioning
confidence: 99%
“…The main impact deriving from all of these crises was the lowering of demand for raw materials and primary commodities and this had a strong direct impact on economic growth. The decline in exports of primary commodities resulted, in turn, in a dive in volumes of manufacturing exports (Khalafalla and Webb 2001;Hussain, Mlambo, and Oshikoya 1999). The current crisis has resulted in decreased demand for commodity exports and traderelated services, especially in the outward-oriented emerging economies (Borchert and Mattoo 2009).…”
Section: Analysis Of Industrial Structuresmentioning
confidence: 99%